Factors affecting the expenditure of treatment of four selected health complaints in the Province of Quezon Philippines - Gurung, Chitra Kumar
The objectives of this study were: a) to determine and compare the treatment of expenditure and its components of four different health complaints according to different age and sex groups, and b) to determine the factors which significantly affect the treatment expenditure for the same health complaints. The data for this study was culled from the Household Health Expenditures Survey conducted in Quezon Province of the Philippines. The HHE Survey was conducted by using stratified random sampling technique and data were collected by interview method. In the survey 9612 individuals were enumerated from 1728 households. Of these there were 1045 cases of the four selected health complaints namely: acute respiratory infection (ARI), fever, diarrhea and flu. This subset of cases were analyzed for this study. The weighted mean, median and confidence interval estimates were used to determine the total treatment expenditure, the expenditure per day and the components of the treatment expenditure of the four health complaints for different age sex groups. Comparison of the mean and media were made by using nonparametric tests namely the median test, Mann Whitney test and Kruskal Wallis test. To identify the factors affecting total expenditure of treatment, multiple regression analysis was carried out. The results of the study showed that diarrhea had the highest treatment expenditure compared to the other three health complaints. Among the different components of treatment expenditure, the expenses for drugs was several times higher compared to all other components. All independent variables namely education, occupation, household size, family income and place of residence taken altogether were significant predictors of total expenditure. Income had a direct relationship with treatment expenditure while household size was found inversely related to treatment expenditure. Cases from urban area generally spent more compared to those from rural areas. The estimates of treatment expenditure and the factors affecting it differed according to the type of health complaint as well as for different sub-groups of age and sex.